Who coupled which stream(s)? Policy entrepreneurship and innovation in the energy–water nexus in Gujarat, India. (19th June 2019) - Goyal, Nihit; Howlett, Michael; Chindarkar, Namrata
Summary: Although policy entrepreneurship is essential for fostering policy innovations to achieve sustainable development, the literature has conflated different types of entrepreneurship and disaggregated it using inconsistent terminology. We conceptualize entrepreneurship using a six‐stream variant of the multiple streams framework (MSF)—which addresses key limitations of the original MSF—to examine entrepreneurial activities in the case of the Jyotigram Yojana, a widely recognized policy innovation for managing the energy–water nexus in Gujarat, India. We find that whereas policy and political entrepreneurship no doubt played a significant role in coupling the streams and fostering this policy innovation, the process broker, program champion, and technology innovator were also important in policy formulation, implementation, and "success." We conclude that the six‐stream variant of MSF is useful for identifying and distinguishing various types of entrepreneurship involved in policy innovation for sustainability.